The Existence of Arabic Language Learning in Ampel Village Surabaya: A Historical-Pedagogical Analysis - Fahmi, Kaula; Hasanah, Saedah; Wahyudi, Johan; Saekhudin, Akhmad (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2022)
This paper shows that Arabic language learning in Ampel Village, Surabaya has been going on for centuries and has undergone various transformations along with the changing times. In the early days, Arabic language learning was more informal and conducted in mosques and the homes of religious leaders. The curriculum taught was very thick with religious values and Islamic culture. Along with the times, formal educational institutions such as pesantren and schools began to play an important role in the development of Arabic language learning. The curriculum taught is increasingly diverse, covering aspects of linguistics, literature, and Islamic sciences. This research concludes that Arabic language learning in Ampel Village is an integral part of the history and identity of the local community. Despite facing various challenges, the spirit to learn Arabic remains alive among the people of Ampel Village. The results of this study are expected to contribute to the development of an Arabic language learning curriculum that is relevant to the context of the times and enrich the scientific treasury on the history of Islamic education in Indonesia.